Assessment of swine-specific bacteriophages of Bacteroides fragilis in swine farms with different antibiotic practices - Yuranan Leknoi (2018)
© IWA Publishing 2017. We assessed the occurrence and specificity of bacteriophages of Bacteroides fragilis in swine farms for their potential application in microbial source tracking. A local B. fragilis host strain, SP25 (DSM29413), was isolated from a pooled swine feces sample taken from a non-antibiotic farm. This strain was highly specific to swine fecal materials because it did not detect bacteriophages in any samples from human sewage, sheep, goats, cattle, dogs, and cats. The reference B. fragilis strain, RYC2056, could detect phages in swine samples but also detected phages in most human sewage and polluted urban canal samples. Phages of SP25 exist in the proximity of certain swine farms, regardless of their antibiotic use (p > 0.05). B. fragilis strain SP25 exhibited relatively high resistance to most of the veterinary antimicrobial agents tested. Interestingly, most farms that were positive for SP25 phages were also positive for RYC2056 phages. In conclusion, the swine-specific SP25 strain has the potential to indicate swine fecal contamination in certain bodies of water. Bacterial isolates with larger distributions are being studied and validated. This study highlights the importance of assessing the abundance of phages in local swine populations before determining their potential applicability for source tracking in local surface waters.